Advances in Structural Design and Numerical Modelling of Composite Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Special Issue aims to provide a platform for researchers and practitioners to share their state-of-the-art findings, novel concepts, and innovative solutions addressing the challenges associated with the design and modelling of composite materials. Contributions are solicited on a wide range of topics, including but not limited to composite materials characterization, failure analysis, modeling techniques, multiscale modeling, and experimental validation.